2003
DOI: 10.1021/la027081s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Composition and Matrix Polarity on Network Development in Organogels of Poly(ethylene glycol) and Dibenzylidene Sorbitol

Abstract: Dibenzylidene sorbitol (DBS) is a low-molecular-weight organic molecule that can gel a variety of organic solvents and polymers by self-organizing into a three-dimensional nanofibrillar network through hydrogen-bonding and phenyl interactions. In this work, we investigate the composition dependence of such “organogels” prepared with poly(ethylene glycol) (PEG) and two PEG derivatives differing in methoxy end- group substitution, which serves to reduce matrix polarity. Transmission electron microscopy reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 62 publications
6
99
1
Order By: Relevance
“…We have anticipated that the behaviour of the DBS is strongly dependent on the polarity of the solvent and this is indeed the case. Wilder et al [22] have shown that even changing the end groups of the polymer solvent (polyethylene glycol) can affect both the kinetics of gel formation and the dissolution temperature by up to 10 8C. Nogales et al reported that the shear-induced anisotropy in DBS/poly(propylene) was only possible during shear flow at temperatures less than 180 8C.…”
Section: Discussionmentioning
confidence: 99%
“…We have anticipated that the behaviour of the DBS is strongly dependent on the polarity of the solvent and this is indeed the case. Wilder et al [22] have shown that even changing the end groups of the polymer solvent (polyethylene glycol) can affect both the kinetics of gel formation and the dissolution temperature by up to 10 8C. Nogales et al reported that the shear-induced anisotropy in DBS/poly(propylene) was only possible during shear flow at temperatures less than 180 8C.…”
Section: Discussionmentioning
confidence: 99%
“…63 It has been reported that using PEG derivatives with a pendant methoxy group at one end tends to enhance the speed of gelation. For example, the nanofibrils of PEG-DBS gel systems were 10-70 nm in diameter with a primary nanofibrillar diameter of 10 nm; identical to those of gels of DBS in low-molar-mass organic solvents.…”
Section: Dbs Gels Formed In a Polymeric Mediummentioning
confidence: 99%
“…The solvent composition greatly affects the formation and property of the gels [22,23]. Two kinds of solvent systems for the MDBS gels were investigated in this work.…”
Section: Effect Of Solvent Composition Of the Supramolecular Gels Onmentioning
confidence: 99%